Web-Based Village Inventory Management Information System - Moh Anshori Aris Widya; Ines Cyndria Priawati (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Computer technology is something that is highly coveted by every organization, because it can facilitate work, speed up the process, and others. The need for a computer as a problem solving tool quickly and can not be denied. With this problem, the author offers the Village Inventory Information System to the Sumbermulyo Village office.In the hope that the application will provide convenience in terms of data collection of village assets contained in the Sumbermulyo Village Office. So, all village asset data will be stored in the system without worrying about the data will be lost.